PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN SAINTIFIK SEBAGAI UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Asep Ainuropik; Inri Rahmawati; abdul rosyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This thesis presents the findings of a study of the scientific approach to students' mathematical communication skills. The study involved an experimental class and control class taken from 6 grade at SMP Negeri 1 Cigugur. Studies conducted using essay test instruments for evaluating mathematical communication skills and a questionnaire to determine the students' response to the scientific approach. From the results of the posttest data analysis by t test, obtained t_hitung = 6.88 and with t_tabel = 1.686. Because 1.686 <6.888, the H1 is accepted. This shows that the mathematical communication skills students acquire the learning of mathematics with scientific approach better than students who received conventional learning. Begitupulla improvement of communication capabilities mathematical experimental class is better than the control class. In addition, the results of questionnaire responses students note that the students showed a positive response to scientific learning.